2019
DOI: 10.1073/pnas.1820424116
|View full text |Cite
|
Sign up to set email alerts
|

Sideways and stable crack propagation in a silicone elastomer

Abstract: We have discovered a peculiar form of fracture that occurs in a highly stretchable silicone elastomer (Smooth-On Ecoflex 00–30). Under certain conditions, cracks propagate in a direction perpendicular to the initial precut and in the direction of the applied load. In other words, the crack deviates from the standard trajectory and instead propagates perpendicular to that trajectory. The crack arrests stably, and thus the material ahead of the crack front continues to sustain load, thereby enabling enormous str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 40 publications
0
29
0
Order By: Relevance
“…[ 26,27 ] As the strain further increases, fiber‐like flaws are generated around the crack tip at the edge of the specimen (Figure 5d,e), followed by the delamination (Figure 5f–h). [ 28 ] The specimen does not fracture during the loading because of the limitation on the maximum displacement (Δ d max = 6.7 mm; gauge length ≈ 6 mm, as shown in Figure S20, Supporting Information) of the test device. During the unloading of the specimen (Figure 5i–l), the local damage can clearly be observed at the crack tip (Figure 5i,j).…”
Section: Resultsmentioning
confidence: 99%
“…[ 26,27 ] As the strain further increases, fiber‐like flaws are generated around the crack tip at the edge of the specimen (Figure 5d,e), followed by the delamination (Figure 5f–h). [ 28 ] The specimen does not fracture during the loading because of the limitation on the maximum displacement (Δ d max = 6.7 mm; gauge length ≈ 6 mm, as shown in Figure S20, Supporting Information) of the test device. During the unloading of the specimen (Figure 5i–l), the local damage can clearly be observed at the crack tip (Figure 5i,j).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, increased disorder may lead to elevated force magnitudes in regions away from the crack tip leading to a more complex fracture pattern and potentially thicker cracks as was observed in Fig.8. Such complex force field distribution in highly anisotropic and disordered networks suggest the possibility of potential crack growth in unusual directions as has been observed recently as sideway cracks in silicone elastomers [36]. The QC methodology may enable systematic discovery of these new patterns.…”
Section: Force Distribution In the Vicinity Of The Crack Tipmentioning
confidence: 69%
“…Further, the area behind the crack-tip behaves elastically due to the offloading of the strain, and ahead of the crack-tip behaves plastically. While crack-tip-blunting is common in viscoelastic polymers, the elastic strain energy is dissipated by the actual propagation of the crack, which results in plastic deformation behind the crack-tip [ 115 , 148 ]. Additional research has shown that cracks in some viscoelastic polymers, such as silicone, can propagate sideways.…”
Section: External Wearable Sensing Technologiesmentioning
confidence: 99%
“…The sideways cracks help dissipate energy and eventually arrest, allowing the crack-tip to sustain the applied load; therefore, the area ahead of the crack-tip remains elastic, allowing for further stretching of the polymer. Sideways cracks were noted to occur in thick samples that underwent tensile testing at low strain rates [ 148 ]. Currently, whether other viscoelastic polymers undergo sideways cracking or if the sideways cracks help to extend the fatigue life of such polymers is unknown.…”
Section: External Wearable Sensing Technologiesmentioning
confidence: 99%